Survival of the Fittest: Resiliency of Private Schools Amidst the Challenges of the Pandemic - Laigo, Jhanel (Journal of Interdisciplinary Perspectives, 2023)
The COVID-19 pandemic caused immense global disruptions to the education system, placing schools under significant stress. Private schools are more vulnerable to the disruptions caused by the pandemic. There were studies conducted to explore the challenges and resiliency in schools. However, there are no studies conducted to explore how private primary education schools cope with the challenges of the pandemic. This exploratory, retrospective single-case study explored and understood how private schools cope with the challenges of the pandemic. It utilized a semi-structured interview to gather data from a participant who is a school principal in one of the private schools that remained operational despite the challenges of the pandemic. Financial control, instructional, and social mechanisms are the themes that emerged from the data analysis. This paper concludes that private schools employ these mechanisms to have a practical continuity of learning amidst the challenges of the pandemic. The interconnectedness of the mechanisms implied that the resiliency of private schools is a product of concerted efforts from all the members of the education community supported by educational resources. This paper also highlighted some implications for policy-making and educational management, specifically on change and crisis management, and future research directions.